Germination of high Andean treeline species of contrasting environments and along elevational gradients in northwest Argentina - Cuyckens, Griet An Erica (2021)
In mountain ecosystems, temperature and precipitation change along elevation and determine the lower and upper limits of tree species which form forests. Early life performance of tree species has been assessed along elevational gradients as a proxy for several environmental variables. Here, we attempt to answer the following question: How does elevation provenance influence seed mass, viability, and germination of Queñoa (Polylepis spp.)? We worked with four species from two contrasting environments from northwest Argentina. We gathered seeds along elevation gradients, seeds were weighed, tested for viability (Triphenyltetrazoliumchlorid; TTC) and germination percentage in a controlled environment. The analysis was performed using Generalized Linear Models (GLM). We found low germination percentages in all species, probably related to low seed viability. The two species from humid environments had lower seed mass and higher germination percentages than the two species from dry environments. The effect of elevational provenance negatively affected the germination of two species, while the other two species were not affected. We conclude that although the four species studied belong to the same genus, their early life characteristics differ between environments and along elevational gradients according to species. Trends regarding future temperatures suggest increases in germination for two of our study species and no effects on the other two species.